Linguistic attitudes towards the Mayan language by Anglo-Americans, from the linguistic landscape of the city of Mérida, Yucatán (Mexico) - Sima Lozano, Eyder Gabriel (2023)
In the historic center and other spaces in the city of Mérida, there are signs written in Spanish, English and Yucatec Maya, whose information is an attraction for visitors, the people of foreign origin, and English speakers who live in the city. From the point of view of sociolinguistics, this study aims to analyze the linguistic attitudes towards the Mayan language in relation to the linguistic landscape by some English-speaking foreigners in the Yucatecan capital, since there are no studies about this population sector. From a semi-directed interview, the testimonies of speakers who have English as their first language were analyzed. Among the most outstanding attitudes are the critical stance that analyzes the absence of Mayan readers towards their own language, since this landscape is directed towards tourists and not towards Mayan speakers, according to the Anglo-American informants. However, they point out that the strength and presence of Yucatecan Maya as a language of Yucatan is a reality in this context.